Long covid in hospitalized COVID-19 patients: A retrospective cohort study - TEKER SAYIN, AYŞE GÜLSEN (My University, 2022)
Background: We aimed to evaluate the Long COVID frequency, and related factors in patients followed up after hospitalization. Methods: This retrospective cohort study included 133 inpatients with COVID-19 PCR test positivity from Nigde Province, Turkey between 01.01.2021 and 28.02.2021. The characteristics of the patients were recorded by examining the files, and the symptom questioning was made by telephone interviewing with the patients approximately four months after the date of diagnosis. The presence of at least one symptom lasting more than four weeks was described as Long COVID. Results: The frequency of Long COVID was 64.7%. The most common Long COVID symptoms were fatigue (45.9%), respiratory distress (25.6%), and muscle / joint pain (24.8%), respectively. In comparison analysis to identify factors associated with Long COVID; Long COVID was found to be more frequent among women (P=0.04); patients with severe COVID-19 (P<0.01), patients with prolonged hospital stay (P=0.03), patients with the comorbid disease (P=0.03), and Diabetes Mellitus patients (P=0.02). Additionally, the frequency of Long COVID increased as the depression score stated by the person increased after COVID-19 disease (P=0.02). Conclusion: The treatment of COVID-19 patients should not end when they are discharged from the hospital. On the contrary, these patients, especially high-risk patients, should be followed up in post-COVID clinics and rehabilitated physically and psychosocially with a multidisciplinary approach following the recovery period of the acute illness.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Safety Research; General Social Sciences; Health (social science); Public Health, Environmental and Occupational Health; Occupational Therapy; Epidemiology; Social Sciences & Humanities; Health Sciences; Long COVID; COVID-19; Symptom; Hospital; Turkey; Long COVID; COVID-19; Symptom; Hospital; Turkey